Heterologous synapsis and crossover suppression in heterozygotes for a pericentric inversion in the zebra finch - del Priore, Lucía (2015)
In the zebra finch, 2 alternative morphs regarding centromere position were described for chromosome 6. This polymorphism was interpreted to be the result of a pericentric inversion, but other causes of the centromere repositioning were not ruled out. We used immunofluorescence localization to examine the distribution of MLH1 foci on synaptonemal complexes to test the prediction that pericentric inversions cause synaptic irregularities and/or crossover suppression in heterozygotes. We found complete suppression of crossing over in the region involved in the rearrangement in male and female heterozygotes. In contrast, the same region showed high levels of crossing over in homozygotes for the acrocentric form of this chromosome. No inversion loops or synaptic irregularities were detected along bivalent 6 in heterozygotes suggesting that heterologous pairing is achieved during zygotene or early pachytene. Altogether these findings strongly indicate that the polymorphic chromosome 6 originated by a pericentric inversion. Since inversions are common rearrangements in karyotypic evolution in birds, it seems likely that early heterologous pairing could help to fix these rearrangements, preventing crossing overs in heterozygotes and their deleterious effects on fertility.